A day in favela. The role of narration in the field of the pedagogy of marginality - Camilla Boschi (University of Bologna, 2023)
The aim of this article is to share the obtained results by a field research in the favela of Curitiba (Brasile), in order to understand its characteristics, identifying and interpreting the relations that go through a context outside the center, on the edge (Contini, 2014), defining educational inter and transcultural practices (Gramigna 2022). The methodology is qualitative and it uses, (De Conti, 2018). The collection and analysis of data were carried out by a logbook, proponing a Narrative Pedagogy exercise, that promotes a metacognitive and self-hermeneutic process, fundamental to the construction of a dialogue in the epistemic difference. In the final part, dedicated to the discussion of the data, we will try, on one hand, to understand the role of the cooperatives of the catador de lixo (Angelin e Darchanchy, 2018; Marello e Helwege, 2014) in what Freire (1974) defines conscientization process, on the other the emancipatory value of the narration (Demetrio, 2003; Ciotti, 1994) in the retelling of one's own history and in the construction of one's own identity.